Peningkatan Pengetahuan Remaja Tentang Bahaya Akibat Rokok di SMAN 1 Poto Tano Kabupaten Sumbawa Barat - Muhammad Fauzi; Endang Setiawaty; Brilyan Anindya Dayfi (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
Smoking is one of the main risk factors for several chronic diseases that can lead to death. This shows that smoking is a big problem for public health. Apart from the health aspect, smoking also affects the personality of the smoker himself. Usually high school age teenagers are familiar with cigarettes. According to them, if they don't smoke, they are considered not sociable. All of these things are not fully understood by teenagers whose smoking activity has even become a part of their social culture. This community service activity at SMAN 1 Poto Tano, West Sumbawa Regency aims to increase students' knowledge about the dangers of smoking to health. The community service participants are 74 class XII high school students aged 18 years in 2022. This activity begins with filling out a pre-test knowledge questionnaire about the dangers of smoking which is then followed by counselling and re-filling the post-test questionnaire. The results of filling out the questionnaire after counselling has increased, namely 69 students understand the dangers of smoking. During the counselling the students were very enthusiastic in listening to the speaker, for this it is hoped that this activity will be encouraged especially in the world of Education